The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1186/s13705-020-0241-0
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability evaluation of community-based, solar photovoltaic projects in Malawi

Abstract: Background: A novel project sustainability framework is used to evaluate 65 off-grid solar photovoltaic (PV) energy system projects in Malawi. This study addresses PV projects serving rural public facilities, a solution known to have had historical issues with poor sustainability. A recent countrywide program targeting such facilities was evaluated against existing projects to determine whether this latest iteration offered better results. Method: Sustainability is defined at the project-level with metrics jus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…These facts motivate government leaders of countries like this to consider the need to build a sustainable energy network, supported by renewable energy sources. In the work outlined Dauenhauer et al (2020), it is determined that a compendium between solar energy and photovoltaic energy can make the Saudi Arabian electricity grid more sustainable, allowing the satisfaction of its internal demand and even selling energy abroad [36]. Another country analysed in this community is Malawi, where 91% of its population does not have access to electricity.…”
Section: Community Sustainability Of Solar Energy In Different Scenariosmentioning
confidence: 99%
See 1 more Smart Citation
“…These facts motivate government leaders of countries like this to consider the need to build a sustainable energy network, supported by renewable energy sources. In the work outlined Dauenhauer et al (2020), it is determined that a compendium between solar energy and photovoltaic energy can make the Saudi Arabian electricity grid more sustainable, allowing the satisfaction of its internal demand and even selling energy abroad [36]. Another country analysed in this community is Malawi, where 91% of its population does not have access to electricity.…”
Section: Community Sustainability Of Solar Energy In Different Scenariosmentioning
confidence: 99%
“…Another country analysed in this community is Malawi, where 91% of its population does not have access to electricity. A sustainability analysis of 65 off-grid projects is presented in [36]. The electricity supply of these projects is based on photovoltaics panels.…”
Section: Community Sustainability Of Solar Energy In Different Scenariosmentioning
confidence: 99%
“…• Comprehensive sustainability studies of the systems (39)(40)(41)(42) were carried out, covering all major pillars of sustainability relevant to this scale of renewable energy project (technical, economic, social, organisational, and environmental). With an existing data set in place (43 projects from the original study), the inclusion of CEM projects allowed for comparison and analysis of the project-level sustainability of the systems.…”
Section: ) Building On the Foundations Of Cedpmentioning
confidence: 99%
“…In terms of 23 Projects in 17 renewable energy development countries, it was found that almost 21% of projects failed, and only 48% were fully functional. This is due to lack of responsibility and care, low quality/technology used, external influences (political, institutional, environmental) [1]. For the designed generator technology to continue to provide sustainable benefits, it is necessary to have a good design and maintain its capability or reliability.…”
Section: Introductionmentioning
confidence: 99%